IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR: STUDI DESKRIPTIF PENDEKATAN DEEP LEARNING DALAM KERANGKA KURIKULUM MERDEKA BELAJAR - Natsir, Siti Rahmalia (Bajang Institute, 2025)
The independent curriculum is still in the stage of adjustment and implementation in schools. The discourse on changing the independent curriculum to a deep learning approach is a challenge for schools that are in the adjustment stage with the independent curriculum. Currently, schools need to quickly evaluate the implementation of the independent curriculum in order to face the deep learning approach. This research aims to find out the application of mathematics learning in the independent learning curriculum and to find out the deep learning approach within the framework of the independent learning curriculum in the application of mathematics learning in elementary schools. The structure of the independent learning curriculum is intracurricular learning, co-curricular learning and extracurricular learning. The focus in this research is on intracurricular learning. This research method uses mixed methods where mixed methods are a form of triangulation. The instruments used are questionnaires and structured interviews. The results of the study explain that the implementation of Merdeka Curriculum in this school has been aligned with the principles of Deep Learning, which emphasises creativity, critical thinking, and the use of technology in the learning process